2010
DOI: 10.1007/s10571-010-9499-7
|View full text |Cite
|
Sign up to set email alerts
|

Dopaminergic Modulation of Spiny Neurons in the Turtle Striatum

Abstract: Intracellular recordings were obtained from brain slice preparation in neurons of the striatum of the turtle Trachemys scripta elegans, analogous to the mammalian striatum in its topographic organization, synaptic connectivity, cytoarchitecture, and neurochemistry. Here we show that these similarities extend to the electrophysiological properties of its neurons. Biocytin staining revealed that 85% of the recorded neurons were medium spiny neurons while 15% were aspiny neurons. Spiny neurons of the turtle resem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 54 publications
1
7
0
Order By: Relevance
“…In the present study we observed a marked reduction of discharge in lamprey striatal neurons upon D2 receptor activation, a finding that is consistent with results from reptiles, birds and mammals [31], [32], [48]. The D2 receptor agonist, TNPA, shifted the threshold to more depolarized levels for both action potentials and PIR spikes, as well as reducing their amplitudes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In the present study we observed a marked reduction of discharge in lamprey striatal neurons upon D2 receptor activation, a finding that is consistent with results from reptiles, birds and mammals [31], [32], [48]. The D2 receptor agonist, TNPA, shifted the threshold to more depolarized levels for both action potentials and PIR spikes, as well as reducing their amplitudes.…”
Section: Discussionsupporting
confidence: 92%
“…In mammals and birds, selective activation of D2 receptors reduces the overall excitability of striatal projection and interneurons through modulation of intrinsic and synaptic properties [12], [31], [32]. To investigate the effects of D2 receptor activation on lamprey striatal neurons, we applied the selective D2 agonist, TNPA, during whole cell current-clamp recordings.…”
Section: Resultsmentioning
confidence: 99%
“…The former are of two subtypes expressing substance P or enkephalin, respectively. They are similar to the mammalian, avian and reptile spiny projection neurons (Kawaguchi et al 1989;Farries & Perkel, 2000;Farries et al 2005;Barral et al 2010), and project to the lamprey homologues of the globus pallidus and substantia nigra pars reticulata (Stephenson-Jones et al 2011, 2012.…”
Section: Introductionmentioning
confidence: 90%
“…1989; Farries & Perkel, 2000; Farries et al . 2005; Barral et al . 2010), and project to the lamprey homologues of the globus pallidus and substantia nigra pars reticulata (Stephenson‐Jones et al .…”
Section: Introductionmentioning
confidence: 99%
“…The dopamine‐immunoreactive (DA‐IR) neurons and their projection fibers were studied in the cerebellum of various mammals and nonmammalian vertebrates, such as the cat (Nieoullon et al, ), the rat (Panagopoulos et al, ; Ikai et al, ), and the European eel (Roberts et al, ). In the central nervous systems of the reptiles, DA‐IR neurons and fibers were reported in the adult tortoise Geochelone chilensis (Juorio, ), the red‐eared turtle (Smeets et al, ), the turtle Trachemys scripta (Milton and Lutz, ; Barral et al, ), the snake Python regius (Smeets, ), and the lizard Gekko gecko (Russchen et al, ; Stoof et al, ; Smeets et al, ), the lizard Gallotia galloti (Medina et al, ). However, although there were few studies about the distribution of DA in the central nervous systems of reptiles, there were no reports about the DA in the cerebellum of the Yangtze alligator.…”
Section: Introductionmentioning
confidence: 99%